ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA BANK-BANK DI INDONESIA - Bahtiar Usman (Universitas Trisakti, 2003)
Financial ratio's information that come from oompanys financial report usually. Used to evalu-ate company's performance, but if that information used for the prediction of company's profit is very rare to explore this time. The objective of this research is to examine that kind of things and from empiric invention there are some financial ratio that can be used for the prediction of the profit changes in the some in Indonesia like Quick ratio, Gross Yield to Total Asset, Net Income to Total Asset, Leverage Multiplier and Deposit Risk Ratio.Even though the using of this financial ratio can't predict the whole future in comp in Indonesia. This can be happened be cause the lack of data that provide from the research subject and unharmonious from the bank financial report.